Phenolic Compound Induction in Plant-Microbe and Plant-Insect Interactions: A Meta-Analysis - Wallis, Christopher M.; Galarneau, Erin R.-A. (Frontiers in Plant Science, 2020)
Plants rely on a variety of ways to protect themselves from being fed upon, including de novo production of specific compounds such as those termed as phenolics. Phenolics are often described as important in plant health and numerous studies have concluded they increase as a result of insect feeding, pathogen infection, or beneficial microorganism colonization. However, there are some studies reaching differing conclusions. Therefore, meta-analyses were conducted to observe whether common trends in phenolic induction in plants can be made when they become hosts to insects or microorganisms. Four hypotheses were tested. The first was that total phenolics increase as a generic response, and meta-analyses confirmed that this occurs when plants are infested with insects or colonized by bacterial or fungal microorganisms, but not for oomycetes. The second hypothesis was that phenolic induction is different when a beneficial microorganism colonizes a plant versus when a plant is infected by a pathogen. Beneficial bacteria, pathogenic bacteria, and beneficial fungi produced increased phenolic levels in plant hosts, but fungal pathogens did not. The third hypothesis was that insect feeding method on plant hosts determines if phenolics are induced. Chewing induced phenolics but piercing-sucking and wood-boring did not. Lastly, we used meta-analyses to determine if annual or perennials rely on phenolic induction in different amounts, and even though annuals had significantly increased phenolic levels but perennials did not, it was observed that phenolic induction was not statistically different when plant type was considered. These results demonstrate that phenolic induction is a common response in plant hosts exposed to feeding or colonization, with specific exceptions such a pathogenic fungi and piercing-sucking insects.